2000
DOI: 10.1097/00007890-200012270-00017
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Responses to Allogeneic Hepatocytes by Reconstituted Scid Mice, Cd4 Ko, and Cd8 Ko Mice1,2

Abstract: These studies show that both CD4+ and CD8+ T cells (but not host NTC) can independently initiate the rejection of allogeneic hepatocytes. While hepatocyte rejection by isolated CD4+ T cells is not surprising, rejection by CD8+ T cells (in the absence of CD4+ T cells) was unusual, and may explain the failure of "standard" immunosuppressive regimens to suppress acute rejection of allogeneic hepatocytes, as noted in prior studies. Furthermore, NK cells do not appear to be required for either CD4+ T cell or CD8+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 41 publications
5
99
0
Order By: Relevance
“…We have demonstrated that this is due to the relative 'immunoresistance' of the CD8-dependent rejection pathway (3,4). In the current study, we show the important in vivo role of LFA-1 mediated signals on hepatocyteinitiated CD8 + T-cell-dependent alloimmunity.…”
Section: Discussionsupporting
confidence: 53%
“…We have demonstrated that this is due to the relative 'immunoresistance' of the CD8-dependent rejection pathway (3,4). In the current study, we show the important in vivo role of LFA-1 mediated signals on hepatocyteinitiated CD8 + T-cell-dependent alloimmunity.…”
Section: Discussionsupporting
confidence: 53%
“…Whether hepatic engraftment with PEPs results in temporary or long-term allogeneic chimerism or induces tolerance to other allografts, as has been reported in another stem cell transplant model (27), also requires further study. Our observation of allogeneic graft survival is especially intriguing, given that mature allogeneic hepatocytes are vigorously rejected via CD4 and CD8 (nonclassical) pathways when transplanted into the liver, (28,29). Even though the immunological mechanisms leading to graft persistence are not known, our finding that PEP engraftment occurs across a major MHC barrier is very encouraging for the use of allogeneic ES stem cells for treating human disease.…”
Section: Discussionmentioning
confidence: 97%
“…H epatocellular allografts have previously been demonstrated to initiate both CD4 ϩ T cell-dependent and (CD4 ϩ T cell-independent) CD8 ϩ T cell-dependent pathways of allograft rejection (1)(2)(3)(4). The activity of the latter CD8-dependent rejection pathway can be demonstrated following transplantation of hepatocellular allografts into CD4 knockout (KO) 4 mice (1), CD4-depleted C57BL/6 mice (2), and CD8-reconstituted SCID mice (1,4).…”
mentioning
confidence: 99%
“…The activity of the latter CD8-dependent rejection pathway can be demonstrated following transplantation of hepatocellular allografts into CD4 knockout (KO) 4 mice (1), CD4-depleted C57BL/6 mice (2), and CD8-reconstituted SCID mice (1,4). The CD8-dependent pathway is of particular interest because it is resistant to immunosuppressive strategies that readily regulate CD4 ϩ T cell-dependent alloimmune responses (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation